Functional and Structural Differences of Brain in Patients With Vestibular Migraine: A Resting‐State Functional MRI and DTI Study - Ni Liu; Qijun Yu; Shaowei Gan; Yonghui Pan; Zhaowen Qiu (Brain and Behavior, 2025)
ABSTRACT Introduction The pathogenesis of vestibular migraine (VM) still remained unclear. This study used functional magnetic resonance imaging (fMRI) and diffusion tensor imaging (DTI) techniques to study the characteristics of VM brain structure and function changes, to explore the association between those changes and clinical symptoms. Methods 13 VM patients and 12 migraineurs were recruited from a tertiary hospital, while 9 healthy people were selected as controls (HC). All subjects were scanned with fMRI and DTI. The image data were analysed by local consistency (ReHo), functional connectivity (FC), and spatial statistical method based on fiber tracking (TBSS). Results Compared with the migraine group, ReHo in the right dorsolateral middle frontal gyrus, the right inferior frontal gyrus of the insula, and the right inferior frontal gyrus of the trigone in the VM group increased, while the left lingual gyrus, the left posterior cerebellum, and the left fusiform gyrus decreased, and the whole brain FC of the right inferior frontal gyrus in VM group was lower than that in the left middle cingulate gyrus, and lower in the posterior cerebellum than that in the cingulate gyrus. ReHo in the left middle occipital gyrus and left middle temporal gyrus decreased in the VM group compared to the HC group. However, no differences among the three groups were found in DTI. Conclusion There may be vestibular multisensory processing abnormalities in patients with VM, while the regulation of cerebellum may be an important role. fMRI detection may open a new sight for VM diagnosis.